Atmospheric corrosion of reference metals in Antarctic sites - Morcillo, Manuel (2004)
This paper presenta the results obtained at three Antarctic test sites participating in the "Ibero-American Map of Atmospheric Corrosiveness" (MICAT), a project on atmospheric corrosion carried out during the period 1988-1994 at some 70 sites distributed across 12 countries of the Latin-American region, Spain and Portugal. The three Antarctic sites are located near the coastline The singular climatic characteristics of Antarctic regions are related with the purity of the air, the absence of rainfall and the formation of ice on the metallic surfaceduring an important part of the exposure time. However, electrochemical activityis possible below ice layers. This situation affects the structure and morfology of corrosion product films and the resulting corrosion rates of metallic surfaces.